ANALYSIS OF HOUSEKEEPING DUTIES IN MAINTAINING CLEANLINESS AND COMFORT IN THE MITRA MEDIKA PREMIERE HOSPITAL - Suci Ayudiah; Ngatno Sahputra; Farida Hanum (Universitas Dharmawangsa Medan, 2026)
This study aims to analyze the implementation of housekeeping duties in maintaining environmental cleanliness and comfort at Mitra Medika Premiere Hospital. This research is motivated by the importance of hospital environmental cleanliness as part of the quality of healthcare services and the role of housekeeping in creating a safe, comfortable, and hygienic environment for patients. This study used a qualitative descriptive method with data collection techniques through observation and documentation. The results indicate that the implementation of housekeeping duties has been running quite well through the implementation of Standard Operating Procedures (SOPs), clear division of tasks, and coordination between staff. Housekeeping plays a crucial role in maintaining the cleanliness of inpatient rooms, changing linens, managing facilities, and supporting patient comfort. However, several obstacles were encountered in its implementation, such as delays in cleaning under certain conditions and operational limitations. Based on the results, it can be concluded that housekeeping implementation at Mitra Medika Premiere Hospital is in accordance with established standards and has an impact on patient comfort. Improved supervision, discipline, and work evaluation are needed to optimize the quality of hospital cleaning services.